Nanosized vehicles for delivery of photosensitizers in photodynamic diagnosis and therapy of cancer. (September 2018) - Mironov, Andrey F.; Zhdanova, Kseniya A.; Bragina, Natal'ya A.
Abstract : The review summarizes the state of the art of research in the field of nanosized vehicles for delivery of photosensitizers for diagnosis and treatment of malignant neoplasms by photodynamic cancer therapy. Data on the utilization of porphyrin- and phthalocyanine-based photosensitizers in medical practice, the employment of vehicles for their delivery and the development of new effective medications are considered. The review focuses on the most commonly used and proven vehicles based on lipids, lipoproteins and polymers. Strategies for increasing efficiency of nanosized delivery vehicles using various vector molecules specific to different types of cancer are discussed. A systematic analysis of the published data is presented and the available tools for increasing the efficacy of photodynamic therapy by means of nanosized delivery vehicles are assessed. The bibliography includes 188 references.